Polinização e estrutura do androceu em Solanum luridifuscescens bitter (Clado cyphomandra solanaceae): a morfologia da antera prediz a estratégia de polinização? - Bruno Fernandes Falcao (2015)
The flowers of the genus Solanum, in general, have rigid and yellow anthers, which contrast with the perianth color, do not produce nectar, and offer the dry pollen as the only resource, featuring the pollen syndrome. The main pollinators are female's bees that transmit vibrations to anther, causing the release of pollen through the small apical pores. In this paper we studied a population of Solanum luridifuscescens Bitter that flees from this pattern, whose flowers have flexible anthers covered by purple papillae that do not contrast with the corola's color. These features resemble some closely related species which exhibit the pneumatic pollination mechanism, whereby Euglossini males cause compression in the thin anther walls and initiate pollen release without applying vibration to the flowers. In this kind of interaction, the floral scents, act as the main attractives, besides they are the main floral resource, featuring the perfume syndrome. In the Chapter 1 we investigate the reproductive biology and pollination of the population in question, with the main objective of determine the occurrence of this mechanism. The flowers have diurnal anthesis, are hermaphrodites, pentamerous, of purple starry corolla. Last an average of five days, close every night and the style grows during anthesis. Females of six specie's bees visited the flowers and vibrated the anthers to collect pollen. Euglossini males can visit the flowers, but without causing pollen release so, our studies showed the pneumatic mechanism operating only in response to artificial stimuli. In Solanum, a species pollinated by female bees that collect pollen by vibration, the conquest of pneumatic principle can represent an intermediate evolutionary stage between a typical Solanum and those pollinated by Euglossini males. In Chapter 2 we analyze the glandular character of the anthers, in order to elucidate their cellular morphology, seeking evidence of whether the papillae covering the anthers are osmophores. Quick starch consumption, a typical feature in perfume secreting tissues, was observed in the analyzed material. The epidermal connective papillae covering the abaxial surface of the anthers have characteristics commonly found in osmogenic tissue: dense cytoplasm rich in organelles, conspicuous nucleus, numerous mitochondria and lipid droplets in the cytoplasm during anthesis. Small vesicles fuse inside the numerous plastids to form a large globular structure. Several smooth endoplasmic reticulum cisterns are found next to the plastids and the plasma membrane. An amorphous substance of moderate electron density and heterogeneous texture was found in the cuticle. The liberation appears to occur by eccrine processes, but the exact site of transport to the exterior was not found. Although the tests were positive with Sudan and ultrastructural evidence indicates that cells secrete substances of lipidic nature, possibly terpenes, further analysis is still required to confirm the nature of the chemical compounds produced. The acquisition of pneumatic principle of pollination and the development of secretory connective may have occurred more than once in Cyphomandra clade, in view of the non-monophyly of the sections that compose it.